Development of Smart Apps Creator Learning Media Using Problem-Solving Learning Models on Global Warming Materials to Improve Critical Thinking and Problem-Solving Ability - Reza Fahlevi; Tien Aminatun (Postgraduate, University of Mataram, 2023)
This study aims to 1) determine the feasibility of smart apps creator-based learning media used in learning activities, and 2) determine the effectiveness of Smart Apps Creator-based learning media to improve Critical Thinking and Problem Solving skills in Global Warming Materials for Class X Students of SMAN 4 Berau. This research is a Research and Development (R&D) study which refers to the ADDIE model. This research was conducted on 30 students in limited trials and field trials using class X1 and X3 students each of 32 students. The results of the study are that the learning media developed meet the eligibility based on expert judgment and effective learning media in improving critical thinking skills and problem solving abilities. The results of the Manova test show a sig value of 0.000 <0.05, namely Ha is accepted so that there are differences in critical thinking skills and problem-solving abilities between students who use Smart Apps Creator learning media and PowerPoint learning media. The N-gain test of learning media on critical thinking skills gets a score of 68.82 which means it is quite effective and for problem solving skills it gets a score of 91.64 which means it is effective.